Occurrence of the milk-eye catshark Apristurus nakayai (Carcharhiniformes: Pentanchidae) from the South China Sea - Ng, Shing-Lai; Liu, Kwang-Ming; Joung, Shoou-Jeng (Zootaxa, 2023)
The milk-eye catshark Apristurus nakayai Iglésias, 2012 was known from three specimens in the southwestern Pacific Ocean. Six specimens were recently collected from the South China Sea. It belongs to the brunneus group, and superficially resembles A. platyrhynchus Tanaka, 1909. Apristurus nakayai differs from A. platyrhynchus by the following characters: iris shiny white when fresh; body brownish black to black; second dorsal-fin insertion above or slightly in front of the anal-fin insertion; denticles absent inside mouth; and maturing at about 400 mm TL in both sexes. The occurrence of Apristurus nakayai from the South China Sea represents the first record in the northern Hemisphere, and a substantial distributional range extension (ca. 4665 km).